Synthesis of Sodium Alginate Graft Poly (Acrylic Acid-Co-Acrylamide)/ Kaolin Composite Hydrogel and the Study on Its Sorption of Rhodamine B. Issue 7 (September 2015) - Tang, Yaoji; Wang, Qiang; Zhou, Bin; Ma, Dong; Ma, Ze; Zhu, Linhui
Sodium alginate graft poly(acrylic acid-co-acrylamide)/kaolin composite hydrogel was synthesized using ammonium persulfate (APS) as an initiator and N, N'-methylenebisacrylamide (MBA) as a crosslinker. The hydrogel was characterized by infrared spectroscopy, x-ray diffraction, scanning electron microscopy and thermogravimetric analysis. It was used to remove rhodamine B from aqueous solutions. Effects of the adsorbing conditions, including initial concentration of dyestuff, contact time, the dosage of hydrogel, pH value as well as the ionic strength of the solution, on the adsorption capacities were investigated. The adsorption thermodynamics and kinetics were also discussed. The results suggest that the composite hydrogel offers a good potential for rhodamine B removal from water.